Nutrition status of young elite female German football players - Braun, H.; von Andrian-Werburg, J.; Schänzer, W.; Thevis, M. (Pediatric Exercise Science, 2018)
Purpose: To investigate energy intake, energy expenditure, and the nutritional status of young female elite football players using 7-day food and activity records and blood parameters. Methods: A total of 56 female elite football players [14.8 (0.7) y] completed the requested food and activity protocols. Misreporting was assessed by the ratio of energy intake to energy expenditure. The food records were analyzed concerning energy and macronutrient and micronutrient intakes, and energy expenditure was calculated using predictive equations. Hematological data and 25-hydroxyvitamin D serum concentrations were determined. Results: Mean energy intake was 2262 (368) kcal/d [40.5 (7.0) kcal/kg/d] and estimated EE averaged 2403 (195) kcal/d. Fifty-three percent of the players exhibited an energy availability <30 kcal/kg lean body mass; 31% of the athletes consumed <5 g/kg carbohydrates and 34% consumed <1.2 g/kg proteins. A large proportion of players (%) had intakes below the recommended daily allowance of folate (75%), vitamin D (100%), iron (69%), and calcium (59%). Ferritin and 25-hydroxyvitamin D serum levels were below the recommendations of 59% and 38%, respectively. Conclusions: A remarkable number of players failed to meet the energy balance and the recommended carbohydrate and protein intakes. Low iron and 25-hydroxyvitamin D serum levels were observed showing a suboptimal nutrition status of some young female football players. As a consequence, strategies have to be developed for a better information and application of sport nutrition practice among young female football players.